2020
DOI: 10.3390/jcm9030689
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative Transfusion is Independently Associated with a Worse Prognosis in Resected Pancreatic Cancer—a Retrospective Cohort Analysis

Abstract: Backgrounds: Investigate whether intraoperative transfusion is a negative prognostic factor for oncologic outcomes of resected pancreatic cancer. Methods: From June 2004 to January 2014, the medical records of 305 patients were retrospectively reviewed, who underwent pancreatoduodenectomy, pylorus preserving pancreatoduodenectomy, total pancreatectomy, distal pancreatectomy for pancreatic cancer. Patients diagnosed with metastatic disease (n = 3) and locally advanced diseases (n = 15) were excluded during the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 17 publications
(28 citation statements)
references
References 29 publications
0
28
0
Order By: Relevance
“…First, a minimally invasive surgery can enhance postoperative recovery, thereby preserving the patient's functional capacity and initiating adjuvant chemotherapy promptly. Second, LPD has frequently reduced intraoperative bleeding, thus lowering the risk of an intraoperative transfusion, which is known to adversely impact patient survival [9]. Although margin-negative radical pancreatectomy is most effective in treating pancreatic cancer, more than 80% of pancreatic cancer patients have unresectable tumors at the time of diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…First, a minimally invasive surgery can enhance postoperative recovery, thereby preserving the patient's functional capacity and initiating adjuvant chemotherapy promptly. Second, LPD has frequently reduced intraoperative bleeding, thus lowering the risk of an intraoperative transfusion, which is known to adversely impact patient survival [9]. Although margin-negative radical pancreatectomy is most effective in treating pancreatic cancer, more than 80% of pancreatic cancer patients have unresectable tumors at the time of diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…Intraoperative bleeding and blood transfusion are essential considerations in surgical oncology and reported to impact both perioperative and oncologic outcomes [30,31]. The threshold for transfusion of blood at a hemoglobin level < 8 g/dL is widely adopted internationally.…”
Section: Discussionmentioning
confidence: 99%
“…Potential deleterious effects of blood transfusion on oncologic outcomes have been explained by several hypothesized mechanisms, primarily via the induction of immunosuppression [ 88 , 89 ]. In several studies, intraoperative transfusion was found to be one of the independent prognostic factors in resected pancreatic cancer [ 90 , 91 , 92 ]. In addition, a recent meta-analysis [ 35 ] to evaluate potential relationship between perioperative blood transfusion and prognosis of pancreatic cancer surgery also demonstrated detrimental effect of blood transfusion on survival in univariate (68.4%, 13 out of 19 studies) and multivariate analysis (47.4%, 9 out of 19 studies) respectively, showing overall blood transfusion associated with pancreatic cancer surgery can be related to shorter overall survival (pooled odds ratio 2.43, 95% confidence interval 1.90–3.10).…”
Section: Current Literaturementioning
confidence: 99%